History alive! pursuing American ideals : equality, rights, liberty, opportunity, democracy. (Teachers' Curriculum Institute, 2008)
History Alive! Pursuing American Ideals centers on the five founding ideals from the Declaration of Independence: equality, rights, liberty, opportunity, and democracy. Each generation has struggled with these ideals. Some have made little progress toward achieving them. Others have made great progress. This book invites students to become engaged in this struggle, from establishing an American republic to the making of modern America. --Website.